Rozwój socjalistycznej koncepcji podziału i jej wpływ na egalitaryzację społeczeństwa - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1980)
Problems of partition according to work and needs were and still are of a controversial mature. Therefore, the author tries to (present synthetic ally conditions of formulation and development, the very concept, as well as practical implementations of socialist partition principles. Theoretical sources of the Marxian partition concept presented on the ground of ideas of Utopian socialists, above all of Saint-Simon and Owen, are the starting point in considerations. Then the Marxian partition formula presented in „The Critics on Gothian Programme" has been submitted to the analysis. On that background a further modification of partition concepts has been presented, which results from experience gained in practice in the socialism construction in the USSR and the People's Republic of Poland. The elaboration ends with showing the influence of practical realization of socialist (partition (principles on the range of egalitarism in up to now existing socialist societies. Objective and subjectve dfficulities have been also pointed out, which are connected with realization of egalitarism in the scope of equality, of measures, possibilities and life conditions of particular social groups and «classes>.
Development of a Socialist Concept of Parttion and Its Influence on Society's Egalitarism